2017
DOI: 10.5194/acp-2016-1153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring shipping emissions in the German Bight using MAX-DOAS measurements

Abstract: A three-year time series of ground-based MAX-DOAS measurements of NO 2 and SO 2 on the island Neuwerk has been analyzed for contributions from shipping emissions. The 35 1 Atmos. Chem. Phys. Discuss.,

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The increase of SO 2 from above to below capping (factor 10, Section 3.2.2.2) and its small enhancement ratio of 1.20 suggest that land-based emissions dominated the concentration of SO 2 in the lowest atmospheric level. This result might be in large part a consequence of the recent enforcement of the Sulphur Emission Control Area (SECA; active since January 2015, MARPOL Annex VI), as already verified at coastal sites of the North Sea (Kattner et al, 2015;Seyler et al, 2017). On the contrary, ship exhaust appeared to be the main contributor to NO y mixing ratio, leading to E-NO y of 3.45.…”
Section: Ship Emissions In the Arkona Basinmentioning
confidence: 74%
“…The increase of SO 2 from above to below capping (factor 10, Section 3.2.2.2) and its small enhancement ratio of 1.20 suggest that land-based emissions dominated the concentration of SO 2 in the lowest atmospheric level. This result might be in large part a consequence of the recent enforcement of the Sulphur Emission Control Area (SECA; active since January 2015, MARPOL Annex VI), as already verified at coastal sites of the North Sea (Kattner et al, 2015;Seyler et al, 2017). On the contrary, ship exhaust appeared to be the main contributor to NO y mixing ratio, leading to E-NO y of 3.45.…”
Section: Ship Emissions In the Arkona Basinmentioning
confidence: 74%
“…Several studies have confirmed the idea of the O 4 scaling factor and have shown that applying a SF (commonly using a value between 0.75 and 0.9) is indeed necessary (Wagner et al, 2009;Clémer et al, 2010;Irie et al, 2011;Vlemmix et al, 2015b;Wang et al, 2016;Wagner et al, 2019Wagner et al, , 2021. However, other studies have not supported this requirement (Spinei et al, 2015;Ortega et al, 2016;Seyler et al, 2017;Wang et al, 2017a, b). Although the need for an O 4 scaling factor for retrieving aerosol information from MAX-DOAS measurements has been extensively discussed (Wagner et al, 2019), its physical mechanism is not understood and still remains an unresolved issue.…”
Section: Discussionmentioning
confidence: 98%